A Developed Compression Scheme to Optimize Data Transmission in Wireless Sensor Networks - Mazin, Zahraa; Alak, Saif Al- (Iraqi Journal of Science, 2023)
Improving performance is an important issue in Wireless Sensor Networks (WSN). WSN has many limitations including network performance. The research question is how to reduce the amount of data transmitted to improve network performance?                                                                                                                      The work will include one of the dictionary compression methods which is Lempel Ziv Welch(LZW). One problem with the dictionary method is that the token size is fixed. The LZW dictionary method is not very useful with little data, because it loses many bytes when storing small-sized tokens.     From the results obtained, the best compression ratios were in the proposed algorithm. The proposed work suggests using a dynamic size token where the tokens are classified according to their size(one byte, two bytes, or three bytes). The main idea of the proposed work is based on increasing the frequency of data to increase the compression ratio. To increase the frequency of data, the work suggests keeping the amount of incremental reading data instead of keeping the whole real data. Because the climate reading data changes very slowly, the amount of change would be frequent.